Integration of Brassinosteroid Signal Transduction with the Transcription Network for Plant Growth Regulation in Arabidopsis - Sun, Yu (2010)
Brassinosteroids (BRs) regulate a wide range of developmental and physiological processes in plants through a receptor-kinase signaling pathway that controls the BZR transcription factors. Here we use transcript profiling and chromatin-immunoprecipitation microarray (ChIP-chip) experiments to identify 953 BR-regulated BZR1 target (BRBT) genes. Functional studies of selected BRBTs further demonstrate roles in BR-promotion of cell elongation. The BRBT genes reveal numerous molecular links between the BR signaling pathway and downstream components involved in developmental and physiological processes. Furthermore, the results reveal extensive crosstalk between BR and other hormonal and light signaling pathways at multiple levels. For example, BZR1 not only controls the expression of many signaling components of other hormonal and light pathways, but also co-regulates common target genes with light-signaling transcription factors. Our results provide a genomic map of steroid hormone actions in plants, which reveals a regulatory network that integrates hormonal and light signaling pathways for plant growth regulation.